Method for producing a construction device for structuring an embedable material surface, in particular a resin-containing laminate surface, and
By applying an acrylic oligomer adhesion enhancer layer on the laminate carrier material and curing with ultraviolet rays, the high cost and insufficient adhesion problems during the structure of the laminate surface in the prior art are solved, and high mechanical resistance and heat resistance are achieved , reduces production costs and improves molding accuracy.
Patent Information
- Application Number
- CN202380041083.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-19
- Filing Date
- 2023-04-03
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-04-03
AI Technical Summary
The prior art When producing laminates with three-dimensional surface structures, the cost is high, the wear is large, and the adhesion of the resin paint layer is insufficient, resulting in surface defects and shedding problems.
Apply an adhesion enhancer layer composed of acrylic oligomers, reactive diluents and ultraviolet photoinitiators to the carrier material, and cure the paint layer by high-energy radiation, especially ultraviolet irradiation, to form a structure with high mechanical resistance and heat resistance Device.
High mechanical resistance and heat resistance when used in the press are achieved, ensuring good adhesion between the paint layer and the carrier material, avoid falling off, reduce production costs, and improve molding accuracy.
Smart Images

Figure CN119256133A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a construction device for structuring the surface of an embossable material, in particular the surface of a resin-containing laminate, comprising the following steps: providing a web-shaped carrier material made of paper and / or plastic, applying a UV-hardening lacquer layer made of acrylic oligomers on the carrier material, forming a three-dimensional embossed structure in the lacquer layer applied to the carrier material, and during the formation of the embossed structure, curing the lacquer layer by high-energy radiation, preferably UV irradiation.
[0002] In the present invention, high-energy radiation irradiation refers particularly to ultraviolet light (UV light) irradiation and electron beam irradiation.
[0003] The invention further relates to a structuring device for structuring the surface of an embossable material, in particular a resin-containing laminate surface, in particular a structuring device produced according to the method of the invention, which has a web-shaped carrier material made of paper and / or plastic and a lacquer layer made of acrylic oligomer applied to the carrier material, the lacquer layer having a three-dimensional embossed structure. The structuring device can also be referred to as an embossing die. Background Art
[0004] Decorative laminates are known in the prior art, for example as floor coverings or as surfacing material for walls, ceilings or furniture, such as cabinets, workbenches and tabletops or similar furniture. Such laminates usually consist of a substrate, such as a medium-density fiberboard or high-density fiberboard or a resin-impregnated paper layer, a decorative layer and a transparent protective layer applied thereto. The function of the protective layer is to protect the decorative layer from scratches, in particular wear. For example, conventional floor laminate panels have a layer of transparent cured cover paper impregnated with melamine resin as a protective layer. The material of the protective layer usually contains particles that increase the wear resistance, such as quartz or corundum particles.
[0005] In order to accurately imitate the look and feel of natural materials such as wood flooring or stone slabs with decorative laminates, such laminates in the prior art have a three-dimensional surface structure, which preferably corresponds to the printed image of the laminate decorative layer. For example, in order to imitate a wooden board, when pressing a laminate structure containing a wood decorative paper, indentations are embossed in the transparent protective layer, wherein the indentations substantially overlap the wood pores depicted on the wood decorative paper. The formation of such indentations corresponds to the displayed pores and is also referred to as synchronized pores in the professional field.
[0006] Decorative laminates with multicolored or monochromatic decorations (unique decorations, Unidekoren) are also known in the prior art, for example, tabletops or tabletop laminates with a transparent protective layer or the uppermost layer provided with a three-dimensional surface structure.
[0007] In order to produce laminates with a three-dimensional surface structure, the prior art uses, for example, pressed sheets with a surface structure formed by engraving. The laminates are produced at high pressure and temperature using so-called short cycle presses (KT presses), wherein the engraved pressed sheet is mounted on a press plate facing the transparent cured protective layer. When pressing the laminates, for example, the temperature exceeds 120° C. and the pressure exceeds 50 bar. The production costs of engraved pressed sheets are very high. In addition, due to the high pressure load, the wear of the pressed sheets is also very high.
[0008] Furthermore, it is known from the prior art to structure the surface of a resin-impregnated laminate by means of a web-shaped structuring device, also referred to as an embossing die, using pressure and temperature, ie to give the laminate surface a three-dimensional surface structure.
[0009] For example, a method for producing such a web-shaped structuring device is described in EP 2 146 805. The method provides for applying a curable coating to a web-shaped plastic film and then bringing it into contact with a structuring roller. During the contact with the structuring roller, the coating is cured by electron or UV radiation, so that the three-dimensional structure is permanently transferred to the coating of the plastic film. The cured coating is then peeled off from the structuring roller together with the plastic film. Here, before curing, the coating contains 20 to 50% of acrylic oligomers, 15 to 35% of monofunctional monomers and 20 to 50% of polyfunctional monomers for crosslinking. The use of electron radiation to cure the coating is associated with high investment costs and high energy consumption. In addition, in the subsequent processing of the method described in EP 2 146 805, it has been shown that the adhesion of various resins or radiation-curing lacquers to the web-shaped carrier material is often insufficient, so that parts of the resin or lacquer are deposited in the structure of the structuring roller and cured there. As a result, the cured coating on the web-shaped carrier material exhibits recurring surface defects. Cleaning the structuring roller to completely remove the resin or lacquer deposits in its structure is very laborious.
[0010] EP 3 720 673 discloses another method for transferring an embossed structure to at least a portion of the surface of a coating agent. The basic steps of the method are to use a composite material consisting of a substrate and an embossed and at least partially cured coating as an embossing die of an embossing tool. The coating agent used to produce the composite coating is a radiation-curable coating agent of a defined composition. EP 3 720 673 teaches that preferably no further layers are present between the substrate and the composite coating. However, internal tests have shown that the method described in EP 3 720 673 does not produce satisfactory adhesion between the substrate and the relatively hard coating; on the contrary, under conventional pressing conditions of a temperature of about 185° C. and a pressure of more than 50 bar, the coating falls off (desorbs) from the substrate when the corresponding composite material is used as an embossing die.
[0011] In DE 10 2013 007 429, it is proposed to use polyethylene terephthalate films (PET films) etched on at least one surface for producing textured surface films or textured embossing dies. The etched PET film should have very good wettability and adhesion to the resin or paint used for coating, so that during the production of the structured surface film or embossing die, no resin or paint deposits can occur on the structuring roller used for structuring. For the etching of the PET film, DE 10 2013 007 429 proposes the use of trichloroacetic acid in the presence of precipitated silica. Although this method of treating PET films can improve adhesion, it is problematic from an environmental point of view. In addition, such films are difficult to obtain on the market. Summary of the invention
[0012] On this basis, the object of the present invention is to provide a method of the type mentioned at the outset, by means of which a structuring device for structuring the surface of embossable materials, in particular the surface of resin-containing laminates, can be produced at low cost, which is characterized by high mechanical and thermal resistance when used in a press. In particular, a corresponding structuring device is to be provided.
[0013] The object of the invention is achieved by a method having the features of claim 1 or a construction device having the features of claim 14. Advantageous embodiments of the solution according to the invention are the solution of claim 1 or claim 14.
[0014] The method according to the invention is characterized in that before applying the UV-hardening lacquer layer, at least one adhesion promoter layer consisting of an acrylic oligomer, a reactive diluent and a photoinitiator which reacts with high-energy radiation, preferably UV radiation, is applied to the carrier material, and the lacquer layer with the embossed structure is irradiated with high-energy radiation, preferably UV radiation, and cured so that in the cured state, the average Martens hardness of the structured device according to DIN EN ISO 14577 is 10 to 80 N / mm 2 , preferably 30 to 80 N / mm 2 , in which an indenter used as a test body for measuring the Martens hardness is pressed into a paint layer surface having an embossed structure.
[0015] By means of at least one adhesion promoter layer (primer layer) according to the invention, it is possible to produce, using the method mentioned at the outset, a construction device for structuring the surface of embossable materials, in particular the surface of resin-containing laminates, in a cost-effective manner, which construction device has high mechanical and heat resistance when used in a press.
[0016] According to the adhesion promoter layer of the present invention, a three-dimensional embossed structure is formed in the paint layer and then the paint layer is partially or completely cured by high-energy radiation, preferably ultraviolet radiation. The paint layer hardened by high-energy radiation, preferably ultraviolet radiation, can adhere well to the carrier material. In this way, whether the cured paint layer is removed together with the carrier material from the embossing device used to form the embossed structure, or the construction device produced in this way is removed from the surface of the material or laminate used for structured, the structured paint layer will not desorb or fall off from the carrier material in a manner visible to the naked eye or in an unacceptable manner.
[0017] The cross-cut test according to DIN EN ISO 2409 (date: June 2013) is often used to determine the adhesion of coatings. Although the test results do not provide any direct measured values, they can be evaluated by comparison with a standard image showing different levels of damage (characteristic values). The standard specifies the use of cutting blades of a specific shape and size as the test device. When measuring with a multi-blade device, a continuous cut strip consisting of multiple parallel cuts is made through the coating to be tested to the substrate. Another cut strip is then made at right angles to it. This results in a grid with a large number of squares, the so-called cross-cut scratch. For the evaluation, a tape with a certain degree of adhesion is pressed onto the cross-cut scratch and then pulled off the surface to remove the detached parts. By comparison with the standard image, characteristic values of Gt0 to Gt5 are obtained, where Gt0 represents low damage with no detachment of any part of the coating and Gt5 represents high detachment or high damage with more than 65% of the coating detached.
[0018] The method of the invention can produce a construction device with very good adhesion of the structured paint layer to the carrier material. The cross-cut test results according to DIN EN ISO 2409 (date: June 2013) show that the cross-cut characteristic value of the construction device produced according to the invention is 0 to less than / equal to 0.5.
[0019] In the case of lacquers that can be hardened by high-energy radiation, preferably UV rays, a wide processing range from elastic to hard is possible for the adhesion promoter layer. In addition, the acrylic oligomer lacquers that can be hardened by high-energy radiation, preferably UV rays, used in the method according to the invention can give the lacquer layer produced therefrom or the embossed structures formed therein a high hardness. According to the invention, in the finished state, the average Martens hardness of the structured device according to DIN EN ISO 14577 is 10 to 80 N / mm 2 , preferably 30 to 80 N / mm 2This has the advantage of increasing the mechanical and thermal resistance of the construction device when used in a heated press. The relatively hard embossed structure can extend the service life of the construction device. Furthermore, the high hardness of the lacquer layer including the embossed structure has the advantage of achieving high forming accuracy, in particular when pressing the negative structure into the surface of the embossable material or the surface of the resin-containing laminate. This makes it possible, for example, to produce correspondingly structured floor panels or laminates with a relatively high surface roughness or roughness depth Rz according to DIN EN ISO 4287.
[0020] When determining the indentation hardness or Martens hardness according to DIN EN ISO 14577, the test force F and the indentation depth h are measured continuously during the loading and unloading phases. The Martens hardness (HM) is defined in N / mm as the ratio of the maximum force F to the corresponding contact area of the test body. 2 The test body (indenter) is a pyramidal or spherical indenter that is slowly pressed into the surface to be tested at a constant speed. The conversion relationship between the indentation depth and the contact surface must be determined for each indenter shape. For the Vickers or Berkovich pyramid indenters commonly used as indenters, the contact surface is calculated by multiplying the square of the indentation depth h by a constant of 26.43. This is the so-called Martens hardness (HM), which is calculated as follows: HM = F / (26.43·h 2 ).
[0021] The Martens hardness was measured using a FischerScope HM2000S measuring device from Helmut Fischer at a temperature of approximately 23°C and a relative humidity of approximately 50%. The measurement was carried out in accordance with DIN EN ISO 14577, with a test range of 300 mN / 20s to a maximum test force of 300 mN.
[0022] According to an advantageous embodiment of the method according to the invention, at least one adhesion promoter layer is applied to the carrier material, with a layer thickness in the range of 0.5 to 12 μm, preferably in the range of 1 to 10 μm, particularly preferably in the range of 2 to 5 μm, based on the dry state of the adhesion promoter layer. The thickness of the applied adhesion promoter layer is preferably as thin as possible. The inventors surprisingly found that in this way a particularly good bond can be achieved between the lacquer layer and the carrier material. The inventors believe that an adhesion promoter layer that is as thin as possible can improve or strengthen the bond between the lacquer layer and the carrier material, because a thin adhesion promoter layer can also form a chemical bond between the substrate surface of the carrier material and the binder of the lacquer layer.
[0023] The adhesion promoter layer is preferably dried or cured to at least touch dry prior to application of the UV curable coating.
[0024] As described above, the at least one adhesion promoter layer applied to the carrier material in the method according to the invention can be specified in more detail, in particular with regard to its layer thickness in the dry state. Alternatively or additionally, the weight per unit area of the at least one adhesion promoter layer in the dry state (coating weight) can be specified in more detail, which can be calculated from the thickness and density of the adhesion promoter applied to the carrier material in the dry state. If the carrier material is made of a film or its surface provided with the adhesion promoter is defined by a film, the weight per unit area of the adhesion promoter in the dry state is, for example, between about 0.3 and 15 g / m 2 In the range of about 1 to 5 g / m 2 If the carrier material is paper, or its surface provided with the bonding agent is made of paper, the weight per unit area of the bonding agent in the dry state is about 1 to 15 g / m 2 In the range of about 4 to 7 g / m 2 within the range.
[0025] Another advantageous design feature of the method according to the invention is that a web-shaped carrier material made of paper and / or plastic, which is at least partially transparent to high-energy radiation, in particular UV light, is used as the web-shaped carrier material, wherein the curing of the lacquer layer is carried out during the formation of the embossed structure by high-energy radiation, preferably UV light, so that the irradiation is carried out at least partially from the side of the carrier material facing away from the embossed structure.
[0026] In this way, the web-shaped carrier material can be moved at a relatively high conveying speed through an apparatus for forming a three-dimensional embossed structure, for example an apparatus equipped with an embossing roller, wherein during the forming of the embossed structure, the initially flowable lacquer layer is hardened sufficiently quickly at a favorable position in the apparatus by at least one high-energy radiation, preferably a UV radiator, so that the carrier material and the lacquer layer with the embossed structure can be pulled or removed from the embossing roller or embossing tool in a dimensionally stable manner. This embodiment of the invention is particularly advantageous in terms of production technology.
[0027] The web-shaped carrier material used in the method according to the invention, which is at least partially transparent to high-energy radiation, in particular to UV rays, can also be referred to as a transparent web-shaped carrier material. A transparent carrier material can be understood as a light-transmissive carrier material, which can be transparent or light-transmissive. Transparent materials allow most of the light to pass through, and usually a small amount of light is absorbed and scattered. Films made of polyethylene terephthalate (PET), polycarbonate (PC) or polymethyl methacrylate (PMMA) are examples of such transparent carrier materials. A characteristic of light-transmissive materials is that, although light can pass through the material, it is scattered in the material. An example of a light-transmissive carrier material is paper, in particular so-called parchment paper, which can be more or less transparent depending on the design. The grammage of the transparent paper can, for example, be between 80 and 180 g / m2 between.
[0028] The web-shaped carrier material used according to the invention may transmit, for example, 60% to 80% of a range of 1500 to 2200 mJ / cm 2 The measured transmitted UV radiation is approximately 900 to 1760 mJ / cm 2 between 1300 and 1500 mJ / cm 2 between.
[0029] Another advantageous design feature of the method according to the invention is that a web material consisting of paper is used as the web-shaped carrier material, wherein an aqueous adhesion promoter is applied to the carrier material to produce an adhesion promoter layer, wherein the adhesion promoter layer is dried at least in the surface area before the UV-hardening lacquer layer is applied thereto, and wherein the drying temperature is between 80°C and 160°C, preferably between 90°C and 140°C, particularly preferably between 100°C and 120°C.
[0030] The water content of the aqueous adhesion promoter increases the adhesion of the adhesion promoter to the paper web fibers. The water content is removed or greatly reduced during the drying process. This results in a relatively thin layer of adhesion promoter, which results in particularly good adhesion between the substrate surface of the web-shaped carrier material (paper) and the binder of the UV-hardening lacquer layer.
[0031] An advantageous variant of the method according to the invention provides for using a plastic film as the web-shaped carrier material, wherein before the UV-hardening lacquer layer is applied to the adhesion promoter layer, the adhesion promoter layer is cured by high-energy radiation, preferably UV radiation, in particular UV-C radiation, at least to such an extent that the adhesion promoter layer is cured on its surface and / or is substantially no longer adhesive, wherein the photoinitiator of the adhesion promoter layer is suitable for absorbing light in the wavelength range from 250 to 350 nm, preferably in the range from 270 to 330 nm, and the adhesion promoter layer is heated at a temperature of 60 to 200 mJ / cm 2 , preferably 100 to 160 mJ / cm 2 Curing occurs at a dose of UV radiation.
[0032] The use of plastic film as web-shaped carrier material offers advantages in terms of material costs and the robustness of the carrier material and thus of the construction device. The adhesion between the substrate surface of the carrier material (plastic film) and the adhesive of the UV-hardening lacquer layer can be improved by pre-hardening or hardening the adhesion promoter layer before applying the UV-hardening lacquer layer on the adhesion promoter layer, so that the surface is solidified and / or substantially non-sticky. This design has the particular advantage that the adhesion promoter can produce an optimal effect directly at the interface, so that high or very good adhesion values can be achieved with relatively small amounts. The photoinitiator of the adhesion promoter layer used according to the present design can cure or at least pre-cure the adhesion promoter layer quickly and energy-efficiently at a specified UV radiation dose, so that the construction device can be produced at a high speed.
[0033] Another advantageous embodiment of the present invention is that the adhesion promoter layer contains 10 to 90% by weight, preferably 40 to 70% by weight of acrylic oligomers, at least 8% by weight, preferably at least 20% by weight of reactive diluents, 0.5 to 10% by weight of ultraviolet radiation reactive photoinitiators, and selectively 0.1 to 3% by weight of one or more additives, which are defoamers and substrate wetting agents, wherein the total amount of all ingredients contained in the adhesion promoter layer is 100% by weight. The acrylic oligomer is preferably at least difunctional or trifunctional, and more preferably higher functional groups. For example, polyurethane acrylate can be used as an acrylic oligomer. Reactive diluents can reduce the viscosity of the adhesion promoter. Low-viscosity adhesion promoters are conducive to forming a thin adhesion promoter layer on the substrate surface of the web-shaped carrier material when a small amount of adhesion promoter is applied. For this reason, the viscosity of the adhesion promoter is preferably reduced to a minimum.
[0034] The defoamer optionally contained in the adhesion promoter serves to eliminate (dissolve) air or gas inclusions that occur in the liquid adhesion promoter layer. These inclusions occur in the form of foam bubbles, such as microfoam and macrofoam, which can produce pores and pits in the adhesion promoter layer, thereby preventing an optimal bonding effect between the substrate surface of the web-shaped carrier material and the adhesive of the subsequently applied UV-hardening lacquer layer and / or reduce the surface quality of the constructed device.
[0035] The substrate wetting agent optionally contained in the adhesion promoter serves to adjust the interfacial energy between the substrate surface of the web-shaped carrier material and the liquid adhesion promoter. For example, the substrate wetting agent can reduce the interfacial energy or surface tension of the substrate. This makes it possible to optimize the wetting of the substrate surface so that all areas of the substrate surface are uniformly and well wetted, thereby obtaining a well-adherent, non-porous adhesion promoter layer.
[0036] UV curable active diluents that can be used for the adhesion promoter include, for example, 1,6-hexanediol diacrylate (HDDA), dipropylene glycol diacrylate (DPGDA), tripropylene glycol diacrylate (TPGDA), ethylene glycol dimethacrylate (EGDMA), triethylene glycol divinyl ether (DVE-3) or a combination / mixture of these diluents. UV radiation-active photoinitiators that can be used for the adhesion promoter layer include, for example, monoacylphosphine oxide (MAPO), bisacylphosphine oxide (BAPO), 2-hydroxy-2-methylphenylpropanone (HMPP), 1-hydroxycyclohexylphenylketone (CPK) and / or methylbenzoyl formate (MBF).
[0037] Optionally, the adhesion promoter layer may contain aminopropyltriethoxysilane (AMEO), for example in a proportion of 3% to 8% by weight.
[0038] According to another embodiment of the method according to the invention, the lacquer for the UV-hardening lacquer layer contains
[0039] 30 to 95% by weight of acrylic acid oligomers,
[0040] 10 to 70% by weight of monofunctional or polyfunctional monomers,
[0041] 1 to 5 wt % of a photoinitiator, and optionally
[0042] 1 to 6% by weight of one or more additives, including defoamers, substrate wetting agents, release additives, waxes and anti-settling agents, wherein the contents of all components in the UV-hardening lacquer add up to 100% by weight. A UV-hardening lacquer of corresponding composition can give the lacquer layer produced therefrom or the embossed structure formed therein a higher hardness.
[0043] The inventors have surprisingly found that a UV-hardening lacquer composed in this way can be used to cost-effectively produce a construction device of the type mentioned at the outset, in which the embossed structure formed in the lacquer layer has a high hardness and molding accuracy. Therefore, the construction device according to the invention can be used to emboss the surface of an embossable material, in particular a resin-containing laminate surface, into a correspondingly large structural depth without any noticeable or considerable depth loss.
[0044] According to another embodiment, the lacquer for the UV-hardening lacquer layer contains 50 to 95% by weight of acrylic oligomers and / or 10 to 40% by weight of monofunctional or polyfunctional monomers and / or 1 to 3% by weight of photoinitiators and / or 1 to 5% by weight of one or more additives, including defoamers, substrate wetting agents, demoulding additives, waxes and anti-settling agents, the weight sum of all components contained in the UV-hardening lacquer being 100% by weight. By using such a lacquer, a construction device of the type described at the beginning can be realized particularly advantageously. A combination of a higher proportion of acrylic oligomers and monofunctional or polyfunctional monomers can give the embossed structure formed by the lacquer a higher hardness. By adding demoulding additives, the shape-accurate separation of the embossed structure produced in the lacquer layer and the embossing tool, such as an embossing roller, and the shape-accurate separation of the construction device and the surface of the material structured by it can be optimized. The addition of wax as an additive can prevent non-ideal hardening of the lacquer layer surface, which is accompanied by permanent adhesion of the lacquer layer. The interaction of atmospheric oxygen with the applied lacquer layer can lead to non-ideal hardening and permanent adhesion. The addition of an anti-settling agent can prevent one or more specific components in the paint from settling, thereby making the composition, especially the hardness of the produced paint layer or embossed structure, substantially uniform throughout the thickness of the paint layer. Regarding the addition of defoamers and / or substrate wetting agents to the paint composition and their effects, please refer to the above description of the corresponding additives for adhesion promoters to avoid repetition.
[0045] According to another embodiment of the method according to the invention, the photoinitiator of the UV-curing lacquer is selected such that it is suitable for absorbing light with a wavelength in the range of 360 to 420 nm, preferably in the range of 390 to 400 nm. This embodiment of the invention allows for rapid and energy-efficient curing of lacquer layers with embossed structures, so that web-shaped construction devices can be produced at high speeds. In the production method according to the invention, the production or web speed of the construction device can be, for example, in the range of 5 to 15 m / min.
[0046] According to another embodiment of the method of the present invention, the coating used for the adhesion promoter or adhesion promoter layer and / or UV curing coating layer contains urethane acrylate, polyester acrylate, epoxy acrylate or a mixture of two or three of the above acrylates as an acrylic oligomer. These acrylates, especially urethane acrylates, have the characteristics of high toughness, good adhesion and strong wear resistance. Therefore, the construction device produced according to the present invention has corresponding toughness and strength characteristics, so that it has a high firmness when used repeatedly. When structuring the surface of the relevant material, such as the surface of the laminate, this design also helps to improve the forming accuracy or embossing accuracy.
[0047] Another advantageous embodiment of the method according to the invention is characterized in that the UV-hardening lacquer layer is cured by at least one UV light emitting diode radiator, wherein the UV radiation power is between 8 and 16 W / cm2 Between 10 and 14 W / cm 2 This embodiment of the invention makes it possible to produce a construction device of the above-mentioned type in an energy-efficient and cost-effective manner and requires only a relatively low expenditure on equipment technology.
[0048] According to another advantageous embodiment of the method according to the invention, the UV-hardening lacquer layer is subjected to final curing by means of at least one medium-pressure mercury vapor radiator or at least one UV-C radiator, the final curing preferably using 500 to 3000 mJ / cm 2 The design of the present invention makes it possible to produce the above-mentioned type of construction device at a higher production speed. Here, during the forming process of the embossed structure, the UV-hardening lacquer layer applied to the adhesion promoter layer is partially hardened (pre-hardened). Here, the lacquer layer is hardened (partially hardened) to such an extent that the composite material consisting of the web-shaped carrier material, the adhesion promoter and the lacquer layer can be removed from the embossing tool, preferably an embossing roller with high forming accuracy, so that the embossed structure formed into the lacquer layer can be removed from the embossing tool without being lost and the shape is stable. For example, in the first hardening step, about 50% to 80% of the hardness required for complete hardening can be achieved. Then, the composite material removed from the embossing tool is finally hardened (post-hardened) by at least one medium-pressure mercury vapor radiator or at least one UV-C radiator, and the UV radiation dose used is preferably between 500 and 3000 mJ / cm 2 , for example 800 to 2800 mJ / cm 2 , especially 1000 to 2500 mJ / cm 2 Thus, the hardening of the UV-hardening lacquer layer applied to the adhesion promoter layer (pre-hardening) takes place while the lacquer layer is in contact with the embossing tool, whereas the final hardening of the lacquer layer (post-hardening) takes place when the lacquer layer is not in contact with the embossing tool.
[0049] If an embossing roller or a similar device is used to form the embossed structure in the method according to the invention, the structure or composite material formed by the web-shaped carrier material, the adhesion promoter layer and the lacquer layer is preferably guided around the embossing roller at a rotation angle in the range of about 60° to 200°, particularly preferably in the range of about 100° to 180°.
[0050] Another advantageous embodiment of the method according to the invention is characterized in that the embossing structure is formed in the UV-curable lacquer layer in such a way that after the lacquer layer has been cured, its average roughness depth Rz is between 40 and 200 μm, preferably between 100 and 200 μm, according to DIN EN ISO 4287. By means of a correspondingly designed structuring device, a three-dimensional surface structure can be produced on the surface of an embossable material, in particular on the surface of a resin-containing laminate, so that the surface in question has the appearance of a natural material, for example a porous wood grain appearance.
[0051] The amount and weight of the UV-hardening lacquer layer applied depend in particular on the average roughness depth Rz that is required or to be achieved by the cured lacquer layer. In addition, for economic reasons, it is also advantageous to limit the amount of UV-hardening coating applied and the weight of application that follows in order to avoid unnecessary material costs. According to the method of the invention, the weight (applied amount) of the UV-hardening lacquer layer applied is, for example, between 10 and 250 g / m 2 In the range of 25 to 200 g / m 2 In the range of 30 to 100 g / m 2 within the range.
[0052] The mean roughness depth Rz is the arithmetic mean of the individual roughness depths of five consecutive measuring paths in the roughness profile. The mean roughness depth Rz is determined as follows: A defined measuring path on the surface of the workpiece or construction device is divided into seven individual measuring paths of equal size. The roughness depth Rz is determined only via these five measuring paths, since the Gaussian filter to be used requires the first and second half of the measuring path. The difference between the maximum and minimum value of the profile is determined for each individual measuring path. The five individual roughness depths obtained in this way are averaged.
[0053] The measurement of the roughness depth Rz complies with DIN EN ISO 4287 and DIN EN ISO 4288. The measuring equipment used to measure the roughness depth Rz must comply with DIN EN ISO 3274. The profile filter used must comply with DIN EN ISO 11562.
[0054] Another subject of the invention is a structuring device for structuring the surface of an embossable material, in particular a resin-containing laminate surface, in particular a structuring device produced according to the method of one of the above-mentioned embodiments, having a web-shaped carrier material made of paper and / or plastic and a lacquer layer made of acrylic oligomer applied to the carrier material, the lacquer layer having a three-dimensional embossed structure, characterized in that the lacquer layer is connected to the carrier material by at least one adhesion promoter layer, the adhesion promoter layer consisting of acrylic oligomer, reactive diluent and photoinitiator that reacts with UV radiation, wherein in the final state, the structuring device has an average Martens hardness of 10 to 80 N / mm according to DIN EN ISO 14577. 2 , preferably 30 to 80 N / mm 2 , in which an indenter used as a test body for measuring the Martens hardness is pressed into a paint layer surface having an embossed structure.
[0055] The building device according to the invention has the advantages described above in conjunction with the method according to the invention for producing a building device.
[0056] An advantageous embodiment of the construction device according to the invention is characterized in that its adhesion promoter layer contains 10 to 90% by weight, preferably 40 to 70% by weight of acrylic oligomers, at least 8% by weight, preferably at least 20% by weight of reactive diluents, 0.5 to 10% by weight of UV radiation-active photoinitiators, and 0.1 to 3% by weight of one or more additives from the group of defoamers and substrate wetting agents, the weight sum of all components contained in the adhesion promoter layer being 100% by weight. The construction device designed accordingly has high mechanical and thermal resistance and can be used in heated printing presses, such as CPL double-belt printing presses.
[0057] According to another embodiment of the construction device, it is characterized in that, according to DIN EN ISO 4287, the average roughness depth Rz of the paint layer with the embossed structure of the construction device after curing is between 10 and 200 μm, preferably between 40 and 200 μm, and particularly preferably between 100 and 200 μm.
[0058] The application weight of the UV-hardening lacquer layer is, for example, 10 to 250 g / m 2 Between, preferably between 25 and 200 g / m 2 between 30 and 100 g / m 2 between.
[0059] If the web-shaped carrier material of the construction device according to the invention is a plastic film web and is at least partially transparent to high-energy radiation, in particular UV radiation, then this construction device can also be used very well for the so-called CCI method for texturing embossable paint surfaces. CCI is the abbreviation for Calander Coating Inert. The CCI method can be used to provide paintable material sheets such as medium-density fiberboard, high-density fiberboard or plastic board with a high-gloss or matt paint surface. In this method, the material surface, preferably the surface of a wooden material, is dried or hardened by UV light in a calender through a transparent film after the UV paint is applied. In the CCI method, the material surface is preferably first primed and then UV paint is applied as the final paint. The material board with liquid UV paint is directly fed into the calender. There, the surface is hardened under inert conditions. In other words, the painted material board is "package-dried" under a layer of film. The construction device according to the invention with a plastic film web that is at least partially transparent to UV radiation as a carrier material can be used as a film. In this way, material boards with textured paint surfaces can be produced and meet the highest quality requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] The invention is explained in more detail below with reference to schematic diagrams showing exemplary embodiments.
[0061] The figure schematically shows
[0062] Figure 1 : A side view of a method and apparatus for making a structuring device for structuring the surface of an embossable material, in particular a resin-containing laminate surface; and
[0063] Figure 2 : Side view of another embodiment of a method and apparatus for making a construction device for structuring the surface of an embossable material, particularly a resin-containing laminate surface. DETAILED DESCRIPTION
[0064] Figure 1 A device 1 is schematically shown, which can be used to implement the method according to the invention and is explained by way of example, by means of which a three-dimensional structure 2, in particular a reproduction of a wood grain, natural stone, mosaic pattern structure and / or tile pattern structure, can be transferred from a corresponding master structure, for example in the form of an embossing roller 3, to a carrier material 5 coated with a UV-hardening lacquer 4.
[0065] The carrier material 5 is a web-shaped carrier material made of paper and / or plastic that is at least partially transparent to high-energy radiation, in particular ultraviolet radiation. The carrier material 5 is provided in the form of a wound roll 6. For example, a film transparent to ultraviolet radiation made of polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polycarbonate (PC), polymethyl methacrylate (PMMA), polyvinyl chloride (PVC) or other plastics transparent to ultraviolet radiation can be used as the carrier material 5. The film can also be called a transparent film. For example, the thickness of the film is between 50 and 200 μm, preferably between 75 and 125 μm, and particularly preferably between 100 and 125 μm. Alternatively, a transparent paper transparent to ultraviolet radiation can also be used as the web-shaped carrier material 5. For example, the grammage of the paper is between 80 and 180 g / m 2 Between, preferably between 150 and 170 g / m 2 between.
[0066] A UV curing lacquer layer 7 composed of an acrylic oligomer is applied to the carrier material 5, and then a three-dimensional embossed structure is formed in the lacquer layer. According to the present invention, before applying the UV curing lacquer layer 7, at least an adhesion promoter layer 8 composed of an acrylic oligomer, a reactive diluent and a photoinitiator that can react with UV radiation is applied to the carrier material 5.
[0067] For example, the adhesion promoter layer 8 contains 10 to 90 wt %, preferably 40 to 70 wt % of acrylic oligomers, at least 8 wt %, preferably at least 20 wt % of reactive diluents, and 0.5 to 10 wt %, preferably 0.5 to 5 wt % of photoinitiators that react with ultraviolet radiation.
[0068] According to a preferred design, the adhesion promoter used for the adhesion promoter layer 8 or the adhesion promoter layer formed therefrom may have the following composition:
[0069] 60 to 90 wt.% of Ebercryl 4265 (acrylic oligomer or similar urethane acrylate) from Allnex,
[0070] 10 to 30 wt% triethylene glycol divinyl ether (such as Ashland Rapidure DVE-3 or similar monomers),
[0071] 5 to 10 wt% methyl formate (MBF or similar UV-reactive photoinitiator) and
[0072] 0.1 to 3 weight percent of one or more additives, including defoamers and substrate wetting agents, the total weight of all ingredients in the adhesion promoter layer being 100%.
[0073] For example, the photoinitiator is suitable for absorbing light with a wavelength between 250 and 350 nm, preferably between 270 and 330 nm. The adhesion promoter is applied to the web-shaped carrier material 5 by means of an engraved or rubberized application roller 9 , for example.
[0074] If a transparent paper permeable to UV radiation is used as the carrier material 5, the adhesion promoter is preferably applied to the paper web in the form of an aqueous solution to form an adhesion promoter layer 8, and the adhesion promoter layer 8 is thermally dried before the UV curing lacquer layer 7 is applied. For example, drying can be carried out by a radiation heater device 10 facing the adhesion promoter layer 8. Alternatively or additionally, a thermal drying device, such as a radiation heater device (not shown) can also be arranged on the side (bottom or back side) 11 of the paper web 5 facing away from the adhesion promoter layer 8.
[0075] The amount of the aqueous adhesive agent applied is adjusted so that the thickness of the adhesive agent layer 8 in the dry state is in the range of 0.5 to 12 μm, preferably in the range of 1 to 10 μm, and particularly preferably in the range of 2 to 5 μm. In other words, the amount of the aqueous adhesive agent applied to the paper web is adjusted so that, for example, the weight of the adhesive agent layer 8 in the dry state is about 1 to 15 g / m 2 In the range of about 4 to 7 g / m 2 The drying of the adhesion promoter layer 8 is performed at a temperature in the range of 80°C to 160°C, preferably 90°C to 140°C, and in particular 100°C to 120°C, for example.
[0076] If a UV-transmissive plastic film web is used instead of a paper web, the adhesion promoter is preferably applied to the plastic film web in the form of a non-aqueous solution to form an adhesion promoter layer 8, and the adhesion promoter layer 8 is hardened by UV radiation before applying the UV-hardening paint layer 7 until the surface of the adhesion promoter layer 8 is solid and / or essentially non-sticky.
[0077] For example, the bonding agent layer 8 can be at least partially hardened by one or more UV radiators 12, preferably one or more UV-emitting LED radiators, which face the bonding agent layer and / or are arranged on the side (bottom or back) 11 of the plastic film web facing away. For example, with 60 to 200 mJ / cm 2 , preferably 100 to 160 mJ / cm 2 The UV radiation dose hardens the adhesion promoter layer 8.
[0078] Furthermore, as described above, at least partial curing of the adhesion promoter layer 8 by a combination of thermal drying and radiation curing also falls within the scope of the present invention.
[0079] The amount of the non-aqueous adhesion promoter applied is adjusted so that the thickness of the adhesion promoter layer 8 formed thereby in the dry state is in the range of 0.5 to 12 μm, preferably in the range of 1 to 10 μm, and particularly preferably in the range of 2 to 5 μm. In other words, the amount of the non-aqueous adhesion promoter applied to the plastic film web can be adjusted, for example, so that the weight of the adhesion promoter layer 8 in the dry state is about 0.3 to 15 g / m 2 In the range of about 1 to 5 g / m 2 within the range.
[0080] After the adhesion promoter layer 8 has at least partially dried or at least partially hardened, a UV-hardening lacquer made of an acrylic oligomer is applied thereto in order to subsequently form the three-dimensional embossed structure 13 .
[0081] For the UV-hardening lacquer layer 7, a structural lacquer containing the following ingredients is preferably used:
[0082] 30 to 95% by weight of acrylic oligomers,
[0083] 10 to 70% by weight of monofunctional or polyfunctional monomers,
[0084] 1 to 5 wt % of a photoinitiator, and optionally
[0085] 1 to 6 wt. % of one or more additives, including defoamers, substrate wetting agents, release additives, waxes and anti-settling agents, the weight sum of all ingredients contained in the UV-hardening lacquer being 100 wt. %. The photoinitiator of the UV-hardening lacquer is suitable for absorbing light having a wavelength between 360 and 420 nm, preferably between 390 and 400 nm.
[0086] The UV-hardening lacquer layer can be applied by means of a roller or scraper application device, preferably a comma bar application device 14. The comma bar application device 14 has a special scraper, which consists of a roller on which a groove 14.1 of approximately 90° is machined. This groove 14.1 makes the strip scraper look like a comma in the side view (cross-sectional view). The comma bar or the outlet limited by the comma bar and the associated paint box can be adjusted by changing the horizontal and vertical position and by changing the rotation angle. Due to the roundness of the scraper geometry, the shear forces acting on the UV-hardening lacquer are lower than with conventional scrapers. The comma bar system has advantages when applying diluted viscoelastic UV lacquers. When using the comma bar system, the possible changes in application weight and viscosity are particularly large.
[0087] The UV-curing lacquer layer is in a flowable state and therefore contacts the embossing roller 3 or other main structure with a relatively low pressure, so that the UV-curing lacquer can reach the recesses on the outer surface of the embossing roller 3. The composite material consisting of the carrier material 5, the adhesion promoter layer 8 and the lacquer layer 7 is guided around the embossing roller (main structure) 3 at a clearly defined wrap angle (see Figure 1 ). The surrounding angle may be, for example, between 60° and 200°, preferably between 100° and 180°.
[0088] The lacquer layer 7 is hardened in contact with the embossing roller (primary structure) 3, i.e. during the formation of the embossed structure 13, by irradiation with high-energy radiation, preferably UV light, preferably from the radiation-transmissive side of the web-shaped carrier material 5 facing away from the embossed structure 13. The irradiation device used for this purpose is Figure 1 In the figure, 15 is used. In addition to the irradiation from below in the region of the embossing roller 3, the lacquer layer in the region of the embossing roller 3 can also be irradiated from at least one side of the embossing roller 3.
[0089] Preferably, at least one UV-emitting LED radiator is used as the irradiation device 15. The irradiation device 15 emits 8 to 16 W / cm 2 , preferably 10 to 14 W / cm 2 , for example about 12W / cm 2 The paint layer 7 is hardened by the ultraviolet radiation power.
[0090] The lacquer layer 7 reaches a certain degree of hardening (partial hardening) when in contact with the embossing roller (primary structure) 3, so that the composite material consisting of the web-shaped carrier material 5, the adhesion promoter layer 8 and the lacquer layer 7 can be peeled off the embossing roller 3 with high forming accuracy. In particular, after such hardening, the embossed structure 13 formed in the lacquer layer can be removed from the embossing roller 3 without losing depth and maintaining a stable shape. Subsequently, the lacquer layer 7 and the adhesion promoter layer 8 located underneath it are post-hardened (finally hardened) by at least one medium-pressure mercury vapor emitter 16 or at least one UV-C emitter, and the post-hardening or final hardening is preferably between 500 and 3000 mJ / cm 2 The post-hardening or final hardening of the structure device 17 is carried out within a UV radiation dose range of about 200 W / cm 2 The specific area power is completed.
[0091] After final post-hardening (final hardening), the embossed structure 13 of the structuring device 17 produced in this way has an average roughness depth Rz in accordance with DIN EN ISO 4287 in the range from 10 to 200 μm, preferably in the range from 40 to 200 μm, particularly preferably in the range from 100 to 200 μm.
[0092] At the end of the plant 1 for carrying out the production method according to the invention, the finished structured device 17 is wound up.
[0093] Figure 2 The embodiment shown is Figure 1 The disclosed embodiment differs in that the embossing roller 3' is a hollow roller with a radiation-transmissive or transparent roller shell, and at least one radiation device 15 is arranged inside the embossing roller 3' and directed to the contact area of the UV-hardening lacquer layer 7 with the embossing roller 3'.
[0094] Below are some examples and comparative examples of compositions of adhesion promoters used in the method according to the invention or in corresponding tests, as well as radiation-hardening lacquers (covering lacquers) for forming the embossed structure 13 of the construction device 17. In particular, the average values of the Martens hardness and the measured values of the roughness depth Rz of certain web-shaped carrier materials measured in laboratory tests are also provided. In addition, the measured results of the cross-cut test are also provided.
[0095] Adhesion enhancers used in the test of the method of the present invention:
[0096]
[0097] Radiation-curable covering lacquers used in the tests of the method according to the invention:
[0098]
[0099]
[0100] Martens hardness of the constructed device produced according to the present invention and the comparative material:
[0101]
[0102] The Martens hardness in the above-listed examples 1 to 10 was measured using a FISCHERSCOPE HM 2000S measuring device from Helmut Fischer according to DIN EN ISO 14577, with a test range of 300 mN / 20 s. In order to illustrate the influence of the carrier material 5 on the measured surface hardness of the construction device 17, the carrier material (respectively a PET film from Mitsubishi) was also measured separately. The Martens hardness of a radiation-curable lacquer was measured for comparison purposes, i.e. the lacquer (i.e. the cover lacquer C) was separated from a film to which no primer (adhesion promoter) had been previously applied and then measured alone (see Example 10).
[0103] By performing a cross-cut test on the construction devices 17 of Examples 2, 3, 4 and 6 above to determine the adhesion of the paint layer, the characteristic values Gt obtained respectively were all 0. This means that no peeling or significant damage (desorption) of the respective paint layers of the construction devices 17 was detected in these examples. In Examples 5 and 7, the characteristic values Gt of the cross-cut test results were 2 and 1, respectively. However, these Gt values are also good characteristic values, because generally an average characteristic value Gt of at least 3.5 is still classified as a sufficient adhesion value.
[0104] In a comparative test, a UV-hardening lacquer layer consisting of the above-mentioned cover lacquer A, B or C was applied directly to a plastic film (75 μm PET film from Mitsubishi Corporation). ), that is, without using any of the above-mentioned adhesion promoters V1, V2 or V2B, the Gt value in the cross-cut test was 5, showing extremely high desorption properties.
[0105] In order to assess the forming accuracy of the embossed structure 13 of the construction device 17 produced according to the invention, its average roughness depth Rz was measured according to DIN EN ISO 4287 and compared with the average roughness depth Rz of the embossing roller 3 used. One of these embossing rollers had a simulated wood grain structure as the main structure, and the other had a large number of negative pyramids as the main structure.
[0106]
[0107]
[0108] According to the above measured average roughness depth Rz value, it can be seen that the embossed structure of the construction device produced according to the present invention has a very high forming accuracy. It can also be determined from the microscope image that the main structure of the embossing roller 3 can be truly restored in the embossed structure 13 of the radiation-hardened cover lacquer of the construction device 17 by the method according to the present invention.
[0109] The implementation of the invention is not limited to the embodiments shown in the schematic diagram. On the contrary, a number of variants can be envisaged, which use the invention disclosed in the claims even if their design differs from the examples. For example, the adhesion promoter layer 8 can be thermally dried or cured only from one side, for example from the top of the adhesion promoter layer 8, and then the UV-hardening lacquer layer 7 can be applied. In addition, the embossing roller 3 can be equipped with a plurality of radiation devices, preferably LED radiators emitting UV light, which are arranged on the outside and inside of the embossing roller 3 with a transparent roller shell for hardening the lacquer layer 7.
Claims
1. A method for producing a structuring device (17) for structuring the surface of an embossable material, in particular a resin-containing laminate surface, comprising the following steps: A web-shaped carrier material (5) made of paper and / or plastic is provided, to which a UV-curable lacquer layer (7) made of acrylic oligomer is applied, Incorporating a three-dimensional embossed structure (13) into a lacquer layer (7) applied to a carrier material (5), and During the forming of the embossed structure (13), the lacquer layer (7) is cured by high-energy radiation, preferably ultraviolet radiation, The invention is characterized in that before applying the UV-curable lacquer layer (7), at least one adhesion promoter layer (8) consisting of an acrylic oligomer, a reactive diluent and a photoinitiator capable of reacting with high-energy radiation, preferably UV radiation, is applied to the carrier material, and the lacquer layer (7) with the embossed structure (13) is irradiated with high-energy radiation, preferably UV radiation, so that it is cured, so that in the final state, the average Martens hardness of the structured device (17) is 10 to 80 N / mm according to DIN EN ISO 14577. 2 , preferably 30 to 80 N / mm 2 , wherein an indenter used as a test body for measuring Martens hardness is pressed into the surface of a paint layer (7) having an embossed structure (13).
2. The method according to claim 1, characterized in that At least one adhesion promoter layer (8) is applied to the carrier material (5), the layer thickness of the adhesion promoter layer (8) being between 0.5 and 12 μm, preferably between 1 and 10 μm, particularly preferably between 2 and 5 μm, based on the dry state of the adhesion promoter layer (8).
3. The method according to claim 1 or 2, characterized in that: A web-shaped carrier material (5) made of paper and / or plastic, which is at least partially transparent to high-energy radiation, in particular UV rays, is used as the web-shaped carrier material (5), wherein the lacquer layer (7) is cured during the forming process of the embossed structure (13) by irradiation with high-energy radiation, preferably UV rays, so that the irradiation is at least partially carried out from the side of the carrier material (5) facing away from the embossed structure (13).
4. The method according to any one of claims 1 to 3, characterized in that A web of paper is used as a web-shaped carrier material (5), wherein an aqueous adhesion promoter is applied to the carrier material (5) to produce an adhesion promoter layer (8), wherein the adhesion promoter layer (8) is dried at least in the surface area before a UV-curable lacquer layer (7) is applied thereto, and wherein the drying is carried out at a temperature between 80° C. and 160° C., preferably between 90° C. and 140° C., particularly preferably between 100° C. and 120° C.
5. The method according to any one of claims 1 to 3, characterized in that A plastic film is used as a web-shaped carrier material (5), wherein before a UV-curable lacquer layer (7) is applied to an adhesion promoter layer (8), the adhesion promoter layer (8) is hardened by high-energy radiation, preferably UV radiation, at least to a certain extent, so that the surface of the adhesion promoter layer is cured and / or substantially no longer adhesive, wherein the photoinitiator of the adhesion promoter layer (8) is suitable for absorbing light with a wavelength in the range of 250 to 350 nm, preferably in the range of 270 to 330 nm, wherein the adhesion promoter layer (8) is heated at a temperature of 60 to 200 mJ / cm 2 In the range of 100 to 160 mJ / cm 2 Hardening occurs at a dose of UV radiation within a certain range.
6. The method according to any one of claims 1 to 5, characterized in that The adhesion promoter layer (8) comprises 10 to 90% by weight, preferably 40 to 70% by weight, of acrylic acid oligomers, at least 8% by weight, preferably at least 20% by weight, of a reactive diluent, 0.5 to 10% by weight of a photoinitiator capable of reacting with ultraviolet radiation, and Optionally, 0.1 to 3 weight percent of one or more additives, including defoamers and substrate wetting agents, the weight of all ingredients contained in the adhesion promoter layer adding up to 100 weight percent.
7. The method according to any one of claims 1 to 6, characterized in that The lacquer used for the UV-curable lacquer layer (7) comprises 30 to 95% by weight of acrylic acid oligomers, 10 to 70% by weight of monofunctional or polyfunctional monomers, 1 to 5 wt % of a photoinitiator, and optionally 1 to 6% by weight of one or more additives, including defoamers, substrate wetting agents, mold release additives, waxes and anti-settling agents, wherein the amounts of all components present in the UV-curable lacquer add up to 100% by weight.
8. The method according to any one of claims 1 to 7, characterized in that The adhesion promoter layer (8) and / or the lacquer for the UV-curable lacquer layer (7) contains urethane acrylate, polyester acrylate, epoxy acrylate or a mixture of two or three of the above acrylates as acrylic oligomer.
9. The method according to any one of claims 1 to 8, characterized in that The UV-curable lacquer layer (7) is cured by at least one UV-emitting light emitting diode radiator, the UV radiation power of which is between 8 and 16 W / cm 2 Between 10 and 14 W / cm 2 between.
10. The method according to any one of claims 1 to 9, characterized in that The UV-curable lacquer layer is final-cured by at least one mercury vapor medium-pressure radiator (16) or at least one UV-C radiator, preferably with 500 to 3000 mJ / cm 2 range of ultraviolet radiation doses.
11. The method according to any one of claims 1 to 10, characterized in that Photoinitiators for UV-curable lacquers are suitable for absorbing light with a wavelength in the range from 360 to 420 nm, preferably in the range from 390 to 400 nm.
12. The method according to any one of claims 1 to 11, characterized in that The embossed structure (13) is formed in the UV-curable lacquer layer (7) in such a way that after the lacquer layer (7) has hardened, the average roughness depth Rz of the embossed structure (13) is between 10 and 200 μm, preferably between 40 and 200 μm, particularly preferably between 100 and 200 μm according to DIN EN ISO 4287.
13. The method according to any one of claims 1 to 12, characterized in that An embossing roller (3, 3') is used to form the embossed structure (13), wherein a composite material consisting of a web-shaped carrier material (5), an adhesion promoter layer (8) and a lacquer layer (7) is guided around the embossing roller (3, 3'), preferably around an angle in the range of 60° to 200°, particularly preferably between 100° and 180°.
14. A structuring device (17) for structuring the surface of an embossable material, in particular a resin-containing laminate surface, in particular a structuring device produced according to a method according to one of claims 1 to 13, comprising a web-shaped carrier material (5) made of paper and / or plastic and a lacquer layer (7) made of acrylic oligomer applied to the carrier material (5), the lacquer layer having a three-dimensional embossed structure (13), characterized in that The lacquer layer (7) is connected to the carrier material (5) via at least one adhesion promoter layer (8) consisting of an acrylic oligomer, a reactive diluent and a photoinitiator capable of reacting with UV radiation, wherein in the final state the construction device (17) has an average Martens hardness of 10 to 80 N / mm in accordance with DIN EN ISO 14577. 2 , preferably 30 to 80 N / mm 2 , wherein an indenter used as a test body for measuring Martens hardness is pressed into the surface of a paint layer (7) having an embossed structure (13).
15. The construction device according to claim 14, characterized in that After curing, the lacquer layer (5) with the embossed structure (13) has an average roughness depth Rz of between 10 and 200 μm, preferably between 40 and 200 μm, particularly preferably between 100 and 200 μm, according to DIN EN ISO 4287.
Citation Information
Patent Citations
Decorative sheet and method for manufacturing decorative sheet
CN107921768A
Decorated surface-structured wall or floor panel based on a fiber cement sheet
CN109952206A
Release film and method for manufacturing the same
US20120231223A1
